Falls in elder ones - Jeergal, Vasanti A.; Upadhye, Aditi J.; Upadhye, Jayshree J. (International Journal Of Community Medicine And Public Health, 2020)
Background: Falls are a common and serious health problem with devastating consequences. The aim of present study was to find the prevalence of fall in elder ones and search for the causes so that preventive measures can be taken. Methods: 102 participants including males and females were interviewed to find the prevalence and causes of fall from 1st January to 29th February 2020. Data was collected and analyzed. Results: In present study, there was history of fall in 12 (25%) males and 22 (40.74%) females. 3 (6.25%) males and 8 (14.81%) females had history of one fall, 4 (8.33%) males and 9 (16.66%) females had history of 3 falls while 5 (10.41%) males and 5 (9.25%) females had history of more than two falls. In fallens, 10 (83.33%) males and 17 (77.27%) females were above 80 years of age. Fall was associated with fracture in 4 (33.33%) males and 7 (31.81%) females. Diabetes was present in 25 (52.08%) males and 40 (74.07%) females, hypertension was seen in 30 (62.5%) males and 23 (42.59%) females while Coronary heart disease was present in 13 (27.08%) males and 8 (14.81%) females. Conclusions: Prevalence of fall in senior citizens in our study was 25% in males and 40.74% in females. The major contributing factors for fall injuries were aging, visual impairment, previous history of fall, depression, and joint problem. Females had a higher risk of fall compared to males.